2022
DOI: 10.1007/s11600-021-00722-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of debris-induced scour around a slotted bridge pier

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Additionally, the presence of the slot in the pier contributes to a decrease in shear stress in the slotted model which is in good agreement by the findings of [35]. The altered flow regime caused by slots can promote the formation of vortices or eddies, which act as hydraulic barriers against scour [42]. These vortices generate circulating currents that deflect sediment transport away from the bridge foundations, reducing the scour potential [48].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, the presence of the slot in the pier contributes to a decrease in shear stress in the slotted model which is in good agreement by the findings of [35]. The altered flow regime caused by slots can promote the formation of vortices or eddies, which act as hydraulic barriers against scour [42]. These vortices generate circulating currents that deflect sediment transport away from the bridge foundations, reducing the scour potential [48].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, despite these challenges, the use of slots as a scour countermeasure holds great potential. Research studies and field applications have demonstrated the effectiveness of slots in reducing scour depths and extending the service life of bridge foundations [42]. By harnessing the power of hydraulic engineering principles, slots provide a proactive and sustainable solution to mitigate scouring around bridge piers, ensuring the structural integrity and safety of bridges in riverine environments [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terefore, debris accumulation reduces the efciency of sacrifcial piles. In the literature, there are several studies that have investigated the efect of debris accumulation [53][54][55]. It should be noted that in this study, the efect of debris accumulation on the efciency of sacrifcial piles was not studied.…”
Section: Performance Of the Bsspmentioning
confidence: 91%
“…The river's hydro-morphology is driven by both bedload and suspended load, which is especially impactful for engineers. For example, Hamidifar et al (2022) investigated scour countermeasures around piers by using different shapes of slots. Another engineering problem with sediments is how to sample them, particularly in the case of the material moving close to the bed.…”
mentioning
confidence: 99%